2018
DOI: 10.18632/oncotarget.24295
|View full text |Cite
|
Sign up to set email alerts
|

Notoginsenoside R1 ameliorates diabetic encephalopathy by activating the Nrf2 pathway and inhibiting NLRP3 inflammasome activation

Abstract: Numerous researches supported that oxidative stress and inflammation play important roles in the development of diabetic encephalopathy (DEP). Notoginsenoside R1 (NGR1), one major component of Panax notoginseng, is believed to have anti-oxidative, anti-inflammatory and neuroprotective properties. However, its neuroprotective effects against DEP and underlying mechanisms are still unknown. In this study, db/db mice as well as high-glucose (HG)-treated HT22 hippocampal neurons were used as in vivo and in vitro m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 51 publications
3
49
0
Order By: Relevance
“…The activation of NLRP3 inflammatory bodies is closely related to the pathogenesis of DM . In a previous study, NLRP3 inflammasome is activated in the neurons of hippocampus in db/db mice . NLRP3 catalyzes the activation of caspase‐1, thereby promoting the maturation and secretion of IL‐1β and IL‐18 .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The activation of NLRP3 inflammatory bodies is closely related to the pathogenesis of DM . In a previous study, NLRP3 inflammasome is activated in the neurons of hippocampus in db/db mice . NLRP3 catalyzes the activation of caspase‐1, thereby promoting the maturation and secretion of IL‐1β and IL‐18 .…”
Section: Discussionmentioning
confidence: 93%
“…NLRP3 catalyzes the activation of caspase‐1, thereby promoting the maturation and secretion of IL‐1β and IL‐18 . Studies have found that inhibiting NLRP3 inflammasome activation can reduce IL‐1β levels in hippocampus of DM rats, and the expression level of hippocampal IL‐1β is related to cognitive function in DM mice . Quercetin has been shown to increase microglial activation and potently inhibit pro‐inflammatory factors .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, NGR1 ameliorated podocyte injury in rats with diabetic nephropathy through actuating phosphatidylinositol 3'-kinase (PI3K)/protein kinase B (AKT) signal ways [9]. Recent studies showed that NGR1 provided a novel treatment for diabetic kidney disease [10], and NGR1 could ameliorate diabetic encephalopathy [11]. However, seldom studies about the effects of NGR1 on DM were performed till now.…”
Section: Introductionmentioning
confidence: 99%